The Sufism Da'wah of Shaykh KH. M. Luqman Hakim on Urban Muslim Societies - Ali Ridho; Afna Fitria Sari; Muhammad Anshori; Idi Warsah; Mohammed Sharin Haji Masri (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
The condition of urban society is haunted by the turmoil of facing the seemingly erratic turn of the times and experiencing a sense of loss from himself, namely the spiritual side. So, Sufism da'wah was born by KH. M. Luqman Hakim, a charismatic kyai and multidisciplinary religious scholar with the aim  of treating their dry and withered spirit. The purpose of the research is to understand and explore more deeply the Sufism da'wah of KH M. Luqman Hakim in urban Muslim communities. The research is a qualitative phenomenological case study model and primary data is obtained from the interview and the documentation of KH M. Luqman Hakim’s da’wah and his jama'ah. Luqman Hakim’s sufistic recitation congregations spread across 7 major cities in Indonesia, as well as secondary data from scientific journals, books, websites, and documentation. The research found that Sufism da'wah by Shaykh KH M. Luqman Hakim  was carried out in three forms, namely da'wah mimbariyah, da'wah through YouTube, and written da'wah. The main target of his da'wah is the urban Muslim community. The material is tailored to the diverse spiritual capacities of the congregation not only attracts his da’wah to urban Muslims of generations X and Y, but also millennials and Z generations.